AB0542 REACTIONS TO PNEUMOCOCCAL 13-VALENT VACCINE IN PATIENTS WITH BEHCET SYNDROME. (2nd June 2020) - Yurttas, B.; Taflan, S. S.; Saltoglu, N.; Hatemi, G.
Abstract : Background: The European League Against Rheumatism (EULAR) recommends pneumococcal 13-valent (PCV13) and 23-valent vaccines in patients with rheumatic diseases (1). Adverse reactions to 23-valent pneumococcal vaccine were previously reported in patients with Behçet Syndrome (BS) (2). These were proposed to be associated with the pathergy phenomenon which may be observed in patients with BS. Objectives: To determine the frequency of adverse reactions to PCV13 in patients with BS who were candidates for TNF inhibitor treatment, together with ankylosing spondylitis (AS) and rheumatoid arthritis (RA) patients as controls. Methods: All of our patients who are candidates for TNF inhibitor therapy have been offered vaccination with PCV13 since 2016. We surveyed all patients with BS, AS and RA who were vaccinated with PCV13 in our infectious diseases outpatient clinic since 2016. Patients' charts were reviewed and additionally patients were telephoned to identify any adverse local or systemic reactions. Local reactions were defined as redness, swelling, pain, and limitation of arm movement. Systemic reactions were defined as fever, headache, chills, rash, vomiting, joint pain, and muscle pain. Results: A total of 88 patients with BS, 143 patients with AS and 133 patients with RA had been vaccinated in our infectious diseases outpatient clinic. Among these, 55/88 (62%) patients with BS, 86/143 (60%) patients with AS and all 98/143 (68%) patients with RA could be contacted. Twenty-one of 55 (38%) patients with BS, 18/86 (20%) patients with AS and 27/98 (27%) patients with RA reported at least one local and/or systemic reaction after vaccination. Patients with BS reported more systemic reactions than the other two groups (48%, 12%, 23% respectively). On the other hand local reactions were less common among patients with BS (52%, 88%, 77% respectively). The local reactions were confined to erythema at injection site, pain and difficulty in moving among patients with AS and RA while 2 patients with BS had severe papulopustular skin lesions at injection site, in addition to erythema, pain and difficulty in moving. Both of these patients were pathergy positive at the time of the diagnosis. Conclusion: Severe papulopustular skin lesions at PCV13 injection site were observed only, but rarely, in patients with BS. Possibility of recall bias due to the retrospective nature of our study and the lack of other vaccines as controls are limitations of our study. Whether the skin lesions are caused by the skin pathergy reaction needs to be studied prospectively, as the pathergy status at diagnosis may be changed by the time these patients become candidates for TNF inhibitor treatment. References: [1]Furer V, Rondaan C, Heijstek MW, Agmon-Levin N, van Assen S, Bijl M, Breedveld FC, D'Amelio R, Dougados M, Kapetanovic MC, van Laar JM, de Thurah A, Landewé RB, Molto A, Müller-Ladner U, Schreiber K, Smolar L, Walker J, Warnatz K, Wulffraat NM, Elkayam O. 2019 update of EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis. 2020 Jan;79(1):39-52. doi: 10.1136/annrheumdis 2019-215882. Epub 2019 Aug 14. PubMed PMID: 31413005. [2]Saeidinejad M, Kardash S, Connell L. Behcet's disease and severe inflammatory reaction to 23-valent pneumococcal polysaccharide vaccine: a case report and review of literature. Scott Med J. 2018 Sep 25:36933018801215. doi: 10.1177/0036933018801215. [Epub ahead of print] PubMed PMID: 30253703. Disclosure of Interests: Berna Yurttas: None declared, Sitki Safa Taflan: None declared, Nese Saltoglu: None declared, Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker